Annual Report 1990-91 - Planning Commission (Planning Commission, 1990)
The year 1990-91 was the threshold year for the beginning of a new Five Year Plan. The Seventh Plan, which ended in the previous year, provided a promising backdrop for the formulation of a new plan. The overall performance of the economy during the Seventh Plan had been impressive with an average annual growth rate (of GDP at factor cost) of 5.6% as against the target of 5 per cent. Agriculture, despite a run of poor monsoons in the first three years of the Plan, picked up in the remaining two years. Overall industrial production maintained the pace of growth of earlier years.
Government of India Planning Commission
Government of India Planning Commission